ОСОБЕННОСТИ РЕАЛИЗАЦИИ СИСТЕМЫ ОЦЕНКИ ЗАЩИЩЕННОСТИ КРИТИЧЕСКИ ВАЖНЫХ И ПОТЕНЦИАЛЬНО ОПАСНЫХ ОБЪЕКТОВ НА ОСНОВЕ МЕТОДА КЛЕМЕНТСА - ХОФФМАНА - Янников, Игорь Михайлович; Телегина, Марианна Викторовна (Интеллектуальные системы в производстве, 2019)
The paper assesses the existing approaches to the problem of assessing the security of hazardous facilities. It is proposed to carry out an assessment using the system of modeling and calculating the state of protection of hazardous objects developed on the basis of the Clements-Hoffman method, in which a set of threats, protection mechanisms and objects of protection are used to describe the system of protection with full overlap. This system can be used to calculate any type of protection of hazardous objects when entering data on any threats and appropriate means of protection. The paper provides a block diagram of the security system, a functional diagram, the main parameters and stages of development and testing.